Loxodromes On Twisted Surfaces in Euclidean 3-Space - Altın, Mustafa (Fırat University, 2022)
In the present paper, loxodromes, which cut all meridians and parallels of twisted surfaces (that can be considered as a generalization of rotational surfaces) at a constant angle, have been studied in Euclidean 3-space and also some examples have been constructed to visualize and support our theory.